Identification of a Novel Lipid Binding Motif in Apolipoprotein B by the Analysis of Hydrophobic Cluster Domains - Gordon, Scott M. (Biochim Biophys Acta, 2016)
Apolipoprotein B (apoB) is a large amphipathic protein that is the structural scaffold for the formation of several classes of lipoproteins involved in lipid transport throughout the body. The goal of the present study was to identify specific domains in the apoB sequence that contribute to its lipid binding properties. A sequence analysis algorithm was developed to identify stretches of hydrophobic amino acids devoid of charged amino acids, which are referred to as hydrophobic cluster domains (HCDs). This analysis identified 78 HCDs in apoB with hydrophobic stretches ranging from 6 to 26 residues. Each HCD was analyzed in silico for secondary structure and lipid binding properties, and a subset was synthesized for experimental evaluation. One HCD peptide, B38, showed high affinity binding to both isolated HDL and LDL, and could exchange between lipoproteins. All-atom molecular dynamics simulations indicate that B38 inserts 3.7 Å below the phosphate plane of the bilayer. B38 forms an unusual α-helix with a broad hydrophobic face and polar serine and threonine residues on the opposite face. Based on this structure, we hypothesized that B38 could efflux cholesterol from cells. B38 showed a 12-fold greater activity than the 5A peptide, a bihelical Class A amphipathic helix (EC(50) of 0.2658 vs. 3.188 µM; p<0.0001), in promoting cholesterol efflux from ABCA1 expressing BHK-1 cells. In conclusion, we have identified novel domains within apoB that contribute to its lipid biding properties. Additionally, we have discovered a unique amphipathic helix design for efficient ABCA1-specific cholesterol efflux.